(untitled) (Research, Society and Development, 2022)
The complexity of diabetes, its impact on quality of life and the importance of early prevention of its complications are crucial aspects when considering the management of the disease. In this context, herbal medicines appear, medicines obtained using only the active plant raw material that have several advantages over synthetic medicines, such as low cost, easy handling and wide popular approval, thanks to the knowledge of the therapeutic effects of plants. Thus, through an integrative literature review, the present study aimed to understand and better understand the main medicinal plants, popularly used by DM patients, in order to reduce blood glucose. It is known that individuals with diabetes have dysfunctions in their metabolic functioning, so that, due to the need for constant therapy, there are always opportunities to discover effective, easily accessible and low-cost methods that help in the treatment of this disease. Thus, according to Mattos et al. (2018), some of the most cited plants in the literature, given their antidiabetic potential, were: Bauhinia forficata, Aloe vera, Allium sativum, Beta vulgaris, Rauwolfia serpentina, Momordica charantia, Nigella sativa, Trigonella foenum- graecum and Curcuma longa L. In this sense, the need for a good clinical and nutritional anamnesis of the patient is evident. Starting to provide a complementary and integrative service, being aware of the possible side effects that these products may cause.